Seedling Emergence of the Tree Legume Clathrotropis brunnea Amshoff, Endemic from a Colombian Tropical Rainforest - Prato, Andrés I.; Felipe Daibes, L. [UNESP]; Pabón, Miguel A.; Castaño, Alvaro A.; Santos-Heredia, Carolina; Fior, Claudimar S. (Springer Nature, 2021)
Seedling emergence is the main propagation method of forest species. Thus, we aimed to evaluate emergence aspects of the tree legume Clathrotropis brunnea Amshoff (sapán or blackheart sapán), a Fabaceae of high economic value endemic to the Colombian rainforest. We characterized the biometry of legumes and seeds and assessed seedling emergence in three experiments: (1) effect of fruit color and substrate, (2) seed conservation in storage, and (3) presoaking and seed position. Our results showed that seeds of green-yellow fruits have greater length and weight and a water content of up to 53%. Seedling emergence did not differ between green-yellow and dark-brown fruits but did differ with substrate type; nearly 80% of seedlings emerged in the sand substrate (S1), but only 62% emerged in the mixed substrate (S3). Fresh sapán seeds are nondormant, showing a recalcitrant behavior in which seedling emergence decreased after storage in all tested conditions. Both seed-sowing positions allowed an emergence of >80% with a small benefit of the hilum downward, regardless of presoaking treatments. However, these differences did not affect seedling height or biomass after emergence. Our results provide basic knowledge on production of tropical seedlings, seeking species conservation, and use in restoration projects.
Keywords: blackheart sapán; Fabaceae; Magdalena Valley; nursery; recalcitrant seed